Application of integrated adsorption method (oil palm fiber, activated carbon, and ultrafiltration) in hospital wastewater treatment - M. Fazrin Pramavada; Susila Arita; I. Isnurhadi (Jurnal Teknik Kimia, 2024)
Hospital wastewater contains various pollutants including organic and inorganic compounds, heavy metals, and microorganisms which pose environmental and health risks. In Indonesia, the volume of hospital wastewater is increasing, whereas wastewater effluent hasn’t met wastewater quality standard optimally. Conventional wastewater treatments require high-cost, large areas, long operating times, and produce sludge. Previous studies showed that adsorption and filtration effectively decreased Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), and total coliform levels of hospital wastewater. Activated carbon is widely used adsorbent, but oil palm fiber offers higher adsorption capacity due to its cellulose and lignin content. It’s abundant, renewable, low-cost, and eco-friendly adsorbent. Meanwhile, filtration membrane has high adsorption capacity, but it gets saturated quickly and needs pre-treatment process. This study analyzes the effectiveness of integrated adsorption method in hospital wastewater treatment. It was a quasi-experimental study with one group pre-test post-test design. Wastewater from Hospital X in Palembang was treated with oil palm fiber, activated carbon, and ultrafiltration after being deposited for 24 hours. There were four trials. The combination of oil palm fiber, activated carbon, and ultrafiltration shows promising result with removal efficiency percentage of pH by 8.91 %; BOD by 60.53 %; COD by 57.52 %; TSS by 84.21 %; and total coliform by 52.50 %. Each adsorbent has specific role: oil palm fiber significantly decreases BOD (47.37 %) and TSS (80 %) levels; activated carbon effectively decreases COD (58 %) and total coliform (60%) levels; and ultrafiltration effectively decreases TSS level (83.58 %).